Latitudinal trends in the biomass allocation of invasive Spartina alterniflora: implications for salt marsh adaptation to climate warming - Chen, Yasong; Wu, Fujia; Wang, Yueyue; Guo, Yangping; Kirwan, Matthew L.; Liu, Wenwen; Zhang, Yihui (Frontiers in Marine Science, 2024)
Introduction Biomass allocation between aboveground and belowground pools in salt marshes has distinct effects on salt marsh stability, and is influenced by climate warming and reproductive investment. However, the lack of studies on the effect of latitudinal variations in reproductive investments and biomass allocation in salt marshes makes it difficult to explore mechanisms of marsh plant growth to climate warming across geographical scales. The rapid invasion of the salt marsh grass Spartina alterniflora into lower latitude marshes around the world provides an opportunity to investigate biomass allocation and reproductive investment across latitudes, helping to understand how salt marshes respond to climate warming. Methods Therefore, we investigated aboveground biomass (AGB), belowground biomass (BGB), total biomass, sexual reproduction traits (inflorescence biomass, flowering culm), asexual reproduction traits (shoot number, rhizome biomass), among S. alterniflora at 19 sites in 10 geographic locations over a latitudinal gradient of 2000 km from Dongying (37.82°N, high latitude) to Danzhou (19.73°N, low latitude) in China. Results The AGB, BGB, and total biomass displayed hump shaped relationships with latitude, but the BGB: AGB ratio decreased with increasing latitude (i.e. increased linearly with temperature). Interestingly, we found that the BGB: AGB ratio negatively correlated with sexual reproductive investment, but positively correlated with asexual reproductive investment. Discussion While conceptual and numerical models of salt marsh stability and carbon accumulation often infer responses based on aboveground biomass, our study suggests that salt marsh responses to climate warming based on aboveground biomass and static allocations may bias estimates of future salt marsh production driven by climate warming.